Dosa yang Mendatangkan Maut dan Dosa yang Tidak Mendatangkan Maut: Analisa berdasarkan konteks Dosa dalam buku 1 Yohanes - Juan Veron Leuna; Jemmy C. Najoan (Journal on Education, 2023)
The understanding of sin that leads to death and sin that does not lead to death in 1 John. 5:16, 17 is still a topic of debate among Bible scholars. Various opinions, both based on theological interpretations and biblical studies, have emerged to find out the definitions of these two types of sins. Further discussion to understand this verse is needed to gain more thorough understanding. By using several aspects of the exegesis method, the author tries to find out the meaning of sin that leads to death and sin that does not lead to death. The emphasis of this study is on the analysis of sin in the book of 1 John specifically in 2:1 and 3:8 and then compares it with the contents of 5:16, 17. The results of the discussion prove that a sin that leads to death is a condition in which a person commits a sin but does not come by faith in Jesus who is the Mediator and in a situation where a person knowingly commits a sin or acts in violation of God's law continuously. These two conditions will lead to death. while sin that does not bring death is a condition in which a believer who, in his life's journey, could have committed a sin but then came and confessed it before God. That person will get forgiveness from Allah and he will not experience eternal death.